Peranan Guru PAUD Dalam Meningkatkan Minat Siswa Untuk Mengikuti Kegiatan Awal Pembelajaran di TK Mawar Sari Binaan Maleipea - Selfina Wallu; Ni Komang Ayu Sri Lestari; Gaudensiana Delsi; Priska Benedikta Jenahat (Early Childhood Education Development and Studies (ECEDS), 2021)
One of the roles of a teacher is to create a conducive ang enjoyable learning atmosphere, thereby increasing children’s interest in participating in learning activities. However, the observed reality at TK Mawar Sari Binaan Maleipea is that the students are not interested in participating in the early learning activities, which also affects subsequent learning activities. To address this issue, teachers play a significant role in enhancing students’ interest in participating in the early learning activities. This is the primary focus that the researcher in interested in investigating, leading to the necessity for conducting a study with the title: The Role of Early Childhood Education (PAUD) Teachers in Enhancing Students’ Interest to Participate in Early Learning Activities at TK Mawar Sari Binaan Maleipea. With the formulation of the problem, namely what is the teacher's role in increasing students' interest in participating in early learning activities at Mawar Sari Kindergarten Fostered by Maleiea? The purpose of this writing is to find out the teacher's role in increasing students' interest in participating in early learning activities. This research was carried out in the TK Mawar Sari Fostered by Maleipea and the research subjects were assigned to 4 teachers. Data collection techniques are interviews and observation. The data analysis technique used is descriptive qualitative. The results showed that the teacher's role in increasing students' interest in participating in early learning activities was very successful. This can be seen from the teacher's role from the five aspects of children's abilities, namely aspects of concentration, cognitive aspects, emotional aspects, language aspects and social aspects. Based on the results of this study, it can be concluded that the role of the TK Mawar Sari Fostered Maleipea teacher in increasing students' interest in participating in early learning activities.